Pulmonary Manifestations of Primary Immunodeficiency Disorders in Children - Jesenak, Milos; Banovcin, Peter; Jesenakova, Barbora; Babusikova, Eva (Frontiers in Pediatrics, 2014)
Primary immunodeficiencies (PIDs) are inherited disorders in which one or several components of immune system are decreased, missing, or of non-appropriate function. These diseases affect the development, function, or morphology of the immune system. The group of PID comprises more than 200 different disorders and syndromes and the number of newly recognized and revealed deficiencies is still increasing. Their clinical presentation and complications depend on the type of defects and there is a great variability in the relationship between genotypes and phenotypes. A variation of clinical presentation across various age categories is also presented and children could widely differ from adult patients with PID. Respiratory symptoms and complications present a significant cause of morbidity and also mortality among patients suffering from different forms of PIDs and they are observed both in children and adults. They can affect primarily either upper airways (e.g., sinusitis and otitis media) or lower respiratory tract [e.g., pneumonia, bronchitis, bronchiectasis, and interstitial lung diseases (ILDs)]. The complications from lower respiratory tract are usually considered to be more important and also more specific for PIDs and they determinate patients’ prognosis. The spectrum of the causal pathogens usually demonstrates typical pattern characteristic for each PID category. The respiratory signs of PIDs can be divided into infectious (upper and lower respiratory tract infections and complications) and non-infectious (ILDs, bronchial abnormalities – especially bronchiectasis, malignancies, and benign lymphoproliferation). Early diagnosis and appropriate therapy can prevent or at least slow down the development and course of respiratory complications of PIDs.